Undocumented Youth in Limbo: The Impact of America's Immigration Enforcement Policy on Juvenile Deportations - Catalina Amuedo-Dorantes; Thitima Puttitanun (Global Labor Organization (GLO), 2017)
The surge in unaccompanied minor crossings between 2011 and 2014 led to an overwhelming increase in the number of juvenile deportation proceedings, which coincided with a peak in intensified immigration enforcement at the state and local levels. Using data on juvenile deportation proceedings, we examine how tougher immigration enforcement might have influenced judicial rulings on these cases and, ultimately, these youths' ability to stay in the country. We find that the average increase in immigration enforcement over that period is associated with a 15 percent reduction in the share of juvenile cases ending with permission to stay. The result underscores the importance of the immigration policy context in which courts operate on their rulings, even if immigration law is within the jurisdiction of the Federal government. Given the gravity of the circumstances these children are escaping, further attention to how the piecemeal approach to immigration enforcement might impact the protection of their humanitarian rights is warranted.
Keywords: F22; K37; Z18; 330; Interior immigration enforcement; unaccompanied minors; juvenile deportation proceedings; United States